Edukasi Perpajakan di Kalangan Santri melalui Program Sekolah Binaan Politeknik Bosowa - Syarifuddin, Safria; Arifin, Rukminih; Ilham, Ilham; Sari, Sri Nirmala; Afifah, Nurul; Siahaan, Halimah; Denka, Veronika Sari; Gisda, Ardyansyah (Pakis Journal Institute, 2026)
Improving tax education is urgently needed to enable students to manage their personal finances wisely and understand the importance of taxes in community development. This program aims to increase tax compliance and foster a culture of tax awareness as a means of strengthening soft skills in students in grades 1, 2, and 3 of the Al-Mubarak Islamic Boarding School (Islamic Senior High School) in Tobarakka, Wajo. A sound understanding of financial literacy is crucial for preparing students to manage their personal finances and understand the significance of taxes in national development. Through a learning program involving various methods and simulations, students are encouraged to understand basic financial concepts and tax obligations. This program is expected to enhance students' understanding of the importance of intelligent financial management and social responsibility through tax payments. The results of this community service activity confirm the importance of improving education to support the development of students' soft skills, which in turn will help them become more responsible and competitive individuals in the future.